Comprehensive Analysis of TSPAN32 Regulatory Networks and Their Role in Immune Cell Biology - Grazia Scuderi; Katia Mangano; Maria Cristina Petralia; Maria Sofia Basile; Francesco Di Raimondo; Paolo Fagone; Ferdinando Nicoletti (Biomolecules)
Tetraspanin 32 (TSPAN32), a member of the tetraspanin superfamily, is one of several tumor-suppressing subtransferable fragments located in the imprinted gene domain of chromosome 11p15.5, a critical tumor-suppressor gene region. Although the biology of TSPAN32 remains largely unexplored, accumulating evidence suggests its involvement in hematopoietic functions. In this study, we performed a comprehensive analysis of the expression patterns and regulatory roles of TSPAN32. Notably, TSPAN32 is highly expressed in immune cells, particularly in natural killer (NK) cells and CD8+ T cells. The observed downregulation of TSPAN32 during immune cell activation highlights its potential role as a regulator of immune cell activation and metabolic adaptations, which are crucial for effective immune responses against pathogens and tumors. Moreover, the modulation of biological processes following TSPAN32 knockout further supports its critical role in regulating immune cell physiology and responses. These findings not only shed light on the biology of TSPAN32 but also provide the basis for exploring its diagnostic, prognostic, and therapeutic potential in autoimmune and inflammatory disorders, as well as in hematopoietic cancers.